Case report Iatrogenic parasitic leiomyoma: the surgeon's invisible hand - Emery, Shahzia Lambat; Pluchino, Nicola; Martino, Antonella; Mauri, Fabio; Petignat, Patrick; Dubuisson, Jean (Frontiers in Surgery, 2023)
Uterine leiomyoma is the most common benign tumour of the uterus in women of reproductive age. When removed surgically, a mini-invasive procedure is preferentially used (laparoscopic or robotic) and the extraction of the specimen can be managed by power morcellation. In this consecutive case-series, we present three cases of parasitic leiomyoma that appeared following previous surgical management of leiomyoma using the technique of laparoscopic myomectomy with uncontained power morcellation. The time frame in between the initial surgery and the diagnosis of the parasitic leiomyoma was 5.7 years. All three patients were diagnosed with endometriosis: 2 cases prior to the initial surgery and 1 case after the initial surgery. One hypothesis could be that, due to pelvic inflammation, endometriosis is a risk factor for iatrogenic parasitic leiomyoma development in case of uncontained morcellation of leiomyoma during myomectomy.